2020
DOI: 10.1126/sciadv.aba4935
|View full text |Cite
|
Sign up to set email alerts
|

Probing dynamical phase transitions with a superconducting quantum simulator

Abstract: Nonequilibrium quantum many-body systems, which are difficult to study via classical computation, have attracted wide interest. Quantum simulation can provide insights into these problems. Here, using a programmable quantum simulator with 16 all-to-all connected superconducting qubits, we investigate the dynamical phase transition in the Lipkin-Meshkov-Glick model with a quenched transverse field. Clear signatures of dynamical phase transitions, merging different concepts of dynamical criticality, are observed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
71
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 128 publications
(73 citation statements)
references
References 37 publications
1
71
0
1
Order By: Relevance
“…Superconducting circuits can be fabricated into different lattice structures, such as 1D chain, ladder, fully connected graphs, and 2D square lattice. It is a versatile platform for performing various kinds of quantum-simulation experiments, e.g., quantum many-body dynamics [21][22][23][24][25][26][27][28][29][30][31][32][33][34] , quantum chemistry 35,36 , and implementing quantum algorithms [37][38][39][40][41][42] . Our quantum processor with 1D array of superconducting qubits is well suited for studying essential transport properties of spin and energy in BOs and WSL.…”
Section: Introductionmentioning
confidence: 99%
“…Superconducting circuits can be fabricated into different lattice structures, such as 1D chain, ladder, fully connected graphs, and 2D square lattice. It is a versatile platform for performing various kinds of quantum-simulation experiments, e.g., quantum many-body dynamics [21][22][23][24][25][26][27][28][29][30][31][32][33][34] , quantum chemistry 35,36 , and implementing quantum algorithms [37][38][39][40][41][42] . Our quantum processor with 1D array of superconducting qubits is well suited for studying essential transport properties of spin and energy in BOs and WSL.…”
Section: Introductionmentioning
confidence: 99%
“…Superconducting quantum circuits have been used to simulate many physical systems. Spin systems have been a particular focus for quantum simulation through both analog [36][37][38][39] and digital [40,41] methods. However, with regard to digital simulations, a recent study [41] performed on an IBM QPU has concluded that the current state of SC quantum computers is too error-limited to produce dependable quantitative results for larger (six spins or more) systems.…”
Section: Use Casementioning
confidence: 99%
“…Due to the good scalability, long decoherence time, and high-precision full control, the superconducting circuit [15,16] becomes one of the most competitive candidates for achieving the universal quantum computation [31], and it is also a much suitable platform for per-forming quantum simulations [1,[17][18][19][20][21][22][23][24][25][26][27][28][29]. Thus, it is natural to ask whether we can benefit advantages of superconducting circuits to simulate and further study LGTs.…”
Section: Introductionmentioning
confidence: 99%